Cold Code: the global initiative to DNA barcode amphibians and nonavian reptiles. (27th December 2012) - Murphy, Robert W.; Crawford, Andrew J.; Bauer, Aaron M.; Che, Jing; Donnellan, Stephen C.; Fritz, Uwe; Haddad, Célio F.B.; Nagy, Zoltán T.; Poyarkov, Nikolay A.; Vences, Miguel; Wang, Wen‐zhi; Zhang, Ya‐ping
Abstract DNA barcoding facilitates the identification of species and the estimation of biodiversity by using nucleotide sequences, usually from the mitochondrial genome. Most studies accomplish this task by using the gene encoding cytochrome oxidase subunit I (COI; Entrez COX1). Within this barcoding framework, many taxonomic initiatives exist, such as those specializing in fishes, birds, mammals, and fungi. Other efforts center on regions, such as the Arctic, or on other topics, such as health. DNA barcoding initiatives exist for all groups of vertebrates except for amphibians and nonavian reptiles. We announce the formation of Cold Code, the international initiative to DNA barcode all species of these 'cold‐blooded' vertebrates. The project has a Steering Committee, Coordinators, and a home page. To facilitate Cold Code, the Kunming Institute of Zoology, Chinese Academy of Sciences will sequence COI for the first 10 specimens of a species at no cost to the steward of the tissues.